Impulse the science of sex and desire - Grant, Jon E. (Cambridge University Press, 2023)
Sex is everywhere in modern society, yet it remains taboo. We all have questions about sex that are too uncomfortable to ask - how do we get reliable answers? In this go-to guide Drs Grant and Chamberlain use their clinical expertise to answer the questions you wish you could ask about sex. Questions like: Is my sex drive or sex behavior normal? Can someone have too much sex? Or too little? How has Internet dating and pornography changed sex? This go-to guide will help you understand common sexual issues, know when to worry (or not) about different sexual behaviors, and learn how our sex lives adapt to changing technology or in times of crisis. It also provides step-by-step advice for dealing with a range of sexual issues, and practical strategies for strengthening relationships.